Therapeutic effects of herbal medicines in different types of retinopathies: A systematic review - Negin Ansari-Mohseni; Adel Ghorani-Azam; Seyed Ahmad Mohajeri (Mashhad University of Medical Sciences, 2023)
Objective: Retinopathy is an ocular manifestation of systemic diseases such as diabetes and vascular diseases. Herbal drugs have been considered as an effective therapeutic option with minimal side effects for the treatment of retinopathy by reducing the symptoms and improving visual acuity. The purpose of this systematic review was to collect studies on the effectiveness of medicinal plants in the treatment or prevention of retinopathy.Materials and Methods: A systematic literature search was performed in PubMed, Scopus, Google Scholar, and other databases in April 2021 using "herbal products" and "Retinopathy" with all their equivalent and similar terms. For this purpose, human clinical trials with the English language were included and articles with subject irrelevancy were excluded from further evaluation.Results: Overall, 30 articles with 2324 patients were studied for possible effects of herbal therapy on retinopathy. From 30 included articles, different herbal products had been evaluated. Out of 30 selected articles, 11 articles were for the treatment of age-related macular degeneration (AMD), 14 articles covered patients with diabetic retinopathy, and the other five studies were for other retinal disorders. The outcomes in majority of the studies include changes in visual acuity (VA), fundus performance, best-corrected visual acuity (BCVA), central macular thickness (CMT), focal electroretinogram (fERG), supplements and adjuvant medications appeared to be more beneficial in patients with AMD and diabetic maculopathy. Conclusion: Herbal therapy can be considered as a potential candidate in the adjuvant and complementary therapies of retinopathy. However, further studies are required to verify such efficiency.